Protein Kinase D Is Dispensable for Development and Survival of Drosophila melanogaster - Dieter Maier; Anja C. Nagel; Alexandra Kelp; Anette Preiss (G3: Genes, Genomes, Genetics, 2019)
Members of the Protein Kinase D (PKD) family are involved in numerous cellular processes in mammals, including cell survival after oxidative stress, polarized transport of Golgi vesicles, as well as cell migration and invasion. PKD proteins belong to the PKC/CAMK class of serine/threonine kinases, and transmit diacylglycerol-regulated signals. Whereas three PKD isoforms are known in mammals, Drosophila melanogaster contains a single PKD homolog. Previous analyses using overexpression and RNAi studies indicated likewise multi-facetted roles for Drosophila PKD, including the regulation of secretory transport and actin-cytoskeletal dynamics. Recently, involvement in growth regulation has been proposed based on the hypomorphic dPKDH allele. We have generated PKD null alleles that are homozygous viable without apparent phenotype. They largely match control flies regarding fertility, developmental timing and weight. Males, but not females, are slightly shorter lived and starvation sensitive. Furthermore, migration of pole cells in embryos and border cells in oocytes appears normal. PKD mutants tolerate heat, cold and osmotic stress like the control but are sensitive to oxidative stress, conforming to the described role for mammalian PKDs. A candidate screen to identify functionally redundant kinases uncovered genetic interactions of PKD with Pkcδ, sqa and Drak mutants, further supporting the role of PKD in oxidative stress response, and suggesting its involvement in starvation induced autophagy and regulation of cytoskeletal dynamics. Overall, PKD appears dispensable for fly development and survival presumably due to redundancy, but influences environmental responses.